Inter-religious Dialogue for Holistic Development in Ghana: The Role of the Christian Council of Ghana - Joseph Kwadwo Asuming; Cosmas Ebo Sarbah (E-Journal of Religious and Theological Studies)
The need for appreciable inter-religious relations in the increasingly religiously pluralistic world cannot be over-emphasized. This need is even more felt in the various countries where constitutional frameworks have entrenched clauses on individual rights to choice of religion. Going over and above its Christian unity mandate, the Christian Council of Ghana has embarked on an ambitious journey to promote inter-religious encounters. The article, through information obtained from one-on-one interviews of prominent Church leaders and the cross-section of members of the Christian Council of Ghana as well as the critical assessment of the conference and archival materials of the Council, examines the critical role of the Christian Council of Ghana in the promotion of inter-religious dialogue in Ghana. It argues that the Council has developed a relevant inclusive and communal theological position for the inter-religious dialogue for the member churches and individuals. The article, further, argues that critical activities and programmes championed by the Department for Interfaith and Ecumenic Relations of the Christian Council of Ghana in collaboration with the Catholic Bishops’ Conference and the Muslim leadership and other stakeholders in the area of peacebuilding and conflict resolution, good governance, and social development have taken inter-religious dialogue to a highly appreciable heights in Ghana. The paper contributes significantly to the available information on the promotion of interreligious dialogue in Ghana.